OpenStudy (anonymous):

HELP! http://prntscr.com/8ftsei http://prntscr.com/8ftsiv http://prntscr.com/8ftt1w http://prntscr.com/8ftt7i

2 years ago
Mehek (mehek14):

1) x + 5 + 11x - 5

2 years ago
Mehek (mehek14):

5 - 5 = ? 11x + x = ?

2 years ago
OpenStudy (anonymous):

12x?

2 years ago
Mehek (mehek14):

so 12x is your answer for #1

2 years ago
OpenStudy (anonymous):

yes

2 years ago
Mehek (mehek14):

#2 set x = 3 for f(x) f(3) = 3 + 9 = ?

2 years ago
OpenStudy (anonymous):

wait i dont get this one

2 years ago
Mehek (mehek14):

3 + 9 = ?

2 years ago
OpenStudy (anonymous):

oh nvm 12

2 years ago
Mehek (mehek14):

now -3 for x in g(x) g(-3) = 5 * (-3) = ?

2 years ago
OpenStudy (anonymous):

=5

2 years ago
Mehek (mehek14):

no 5 * -3 = -15

2 years ago
Mehek (mehek14):

12 + (-15) = ?

2 years ago
OpenStudy (anonymous):

oh thats true

2 years ago
OpenStudy (anonymous):

=-3

2 years ago
Mehek (mehek14):

so that's ur answer for #2

2 years ago
OpenStudy (anonymous):

yup

2 years ago
Mehek (mehek14):

|dw:1442149403078:dw|

2 years ago
Similar Questions: